Prevalencia de parásitos gastrointestinales en alpacas huacayas (Vicunga pacos) en la comunidad Apagua, cantón Pujilí - Cóndor Tapia, Diana Maribel (2015)
In this paper the prevalence of gastrointestinal parasites in Huacaya Alpacas was determined through the prevalence rate; to collect information, an analysis about the current situation in Apagua Community was set up which obtains the number of Huacayas that live in the area. A coproparasitario examination was carried in the parasitology laboratory at the Technical University of Cotopaxi used the "Method of Faust" which is based on floating eggs of parasites. Once, the identification was established, the results was located in contingency tables for its after tabulation; so the parasitic load was determined where shows that Huacayas have mild parasitism; then, the prevalence of gastrointestinal parasites was finalized and the researcher concluded there is a high prevalence in Nematodirus type spp with 42.11%, Trichuris spp 23.70% and the lowest prevalence Bunostomun type spp 0.90%....